CUSTOMER PERSPECTIVE ON PURCHASE DECISION HALAL PRODUCTS - Muhammad Saputra; Yuniwati; Lislindawati; Yusminar Wahyuningsih (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2023)
The purpose of this study were knowing the effect of brand awareness, religiousity, halal marketing on purchase decision halal products. This study were asosiative research. The populations of this study were all muslim society in Indonesia. Sampling method in this study were nonprobabilty sampling used purposive samling technique. Sample total in this study amounted 100 respondents used slovin formula. The result showed religiousity and halal marketing had effect on purchase decision halal products and there is no effect halal awareness on purchase decision halal products